The Effects of Attitude, Subjective Norm, Moral Norm, Anticipated Affect and Identity Appropriateness on Predicting People's Responses to Two Influential Moral Dilemmas - Yang, Shengyu (IJRDO - Journal of Social Science and Humanities Research, 2020)
To investigate the factors that may influence people’s responses to two influential moral dilemmas (the switch dilemma and the fat man dilemma) which were based on the classic Trolley Problem, 153 participants took part in an online questionnaire study. As expected, most participants chose to press the switch and not to push the fat man. In addition, among the five possible factors, attitude, moral norm and identity appropriateness could significantly predict individuals’ moral decisions towards the two dilemmas. Moreover, the difference measure with action and inaction could explain more variance of the models than the single action measure. The study showed no supportive result for the effects of Dilemma Order and Decision Order.